BACKSLIDING ON CHILDHOOD IMMUNIZATIONS DUE TO ONGOING COVID-19 PANDEMIC: A RETROSPECTIVE STUDY IN BANADIR REGION, SOMALIA - Orey, Fartun Abdullahi H.; Mohamud, Kadra Hassan Sheik; Abdulle, Iftin Abdi Nor; Mohamoud, Jamal Hassan; Garba, Bashiru; Adam, Mohamed Hussein; Dahie, Hassan Abdullahi; Nur, Maryan Abdullahi Sh.; Dirie, Najib Isse (African Journal of Infectious Diseases (AJID), 2023)
Background: SARS-CoV-2 has resulted in a global public health crisis. During the pandemic, considerable delay was observed making it impossible for some children to receive their due vaccines on time. Like most resource-poor countries, COVID-19 pandemic is thought to have a negative impact on Somalia’s immunization coverage. Materials and methods: This study aimed to assess the impact of the COVID-19 pandemic on routine childhood immunization coverage in Somalia. A retrospective comparative cross-sectional approach was employed to investigate the number of under-5-year children who got their immunization from the two major mother and child hospital, (Banadir and SOS in Mogadishu, Somalia from October 2019 to December 2020. To do this, a total of 112, 060 data relating to the routine childhood immunization (measles, polio, whooping cough, hepatitis B, pneumonia, and tuberculosis) were collected from the monthly immunization report-data from the two hospitals. Results: The results showed that all the vaccines except birth vaccines have remarkably dropped with Penta-3 (27%), Penta-2 (11%), measles (10%) and Penta-1 (8%) respectively. However, the birth vaccines (BCG and Polio 0) were not affected as observed in this study. The reduction in children immunization rate in Somalia may be a combination of many other factors, we however recognize that the COVID-19 pandemic may have contributed significantly to this outcome. Conclusion: The government needed to take proactive measures to encourage parents to present their children for immunizations, including increasing community concerning the importance of these routine childhood immunizations despite the ongoing COVID-19 pandemics.